Vasotocin Actions on Electric Behavior: Interspecific, Seasonal, and Social Context-Dependent Differences - Perrone, Rossana; Batista, Gervasio; Lorenzo, Daniel; Macadar, Omar; Silva, Ana (Frontiers in Behavioral Neuroscience, 2010)
Social behavior diversity is correlated with distinctively distributed patterns of a conserved brain network, which depend on the action of neuroendocrine messengers that integrate extrinsic and intrinsic cues. Arginine-vasotocin (AVT) is a key integrator underlying differences in behavior across vertebrate taxa. Weakly electric fish use their electric organ discharges (EODs) as social behavioral displays. We examined the effect of AVT on EOD rate in two species of Gymnotiformes with different social strategies: Gymnotus omarorum, territorial and highly aggressive, and Brachyhypopomus gauderio, gregarious and aggressive only between breeding males. AVT induced a long-lasting and progressive increase of EOD rate in isolated B. gauderio, partially blocked by the V1a AVT receptor antagonist (Manning compound, MC), and had no effects in G. omarorum. AVT also induced a long-lasting increase in the firing rate (prevented by MC) of the isolated medullary pacemaker nucleus (PN) of B. gauderio when tested in an in vitro preparation, indicating that the PN is the direct effector of AVT actions. AVT is involved in the seasonal, social context-dependent nocturnal increase of EOD rate that has been recently described in B. gauderio to play a role in mate selection. AVT produced the additional nocturnal increase of EOD rate in non-breeding males, whereas MC blocked it in breeding males. Also, AVT induced a larger EOD rate increase in reproductive dyads than in agonistic encounters. We demonstrated interspecific, seasonal, and context-dependent actions of AVT on the PN that contribute to the understanding of the mechanisms the brain uses to shape sociality.